Psychometric Validation of the Turkish Motives for Online Gaming Questionnaire (MOGQ) Across University Students and Video Game Players - Evren, Cüneyt; Evren, Bilge; Dalbudak, Ercan; Topçu, Merve; Kutlu, Nilay (Addicta: The Turkish Journal on Addictions, 2020)
The main aim of the current study was to test the factor structure, reliability, and validity of the 27-Item Motives for Online Gaming Questionnaire (MOGQ), a standardized measure to assess seven types of motivation for online gaming. In the present study, participants were assessed with the MOGQ, the nine-item Internet Gaming Disorder Scale- Short Form (IGDS9-SF), and the Electronic Gaming Motives Questionnaire (EGMQ). The mean age and age at first gaming were lower and the socio-demographic factors such as male gender, living alone, having a game console, gaming more than usual in weekends, time spent on the gaming, having problems related with gaming, severity of IGD symptoms, and severity of online gaming motives were higher among the group of gamers than those in the group of students. Confirmatory factor analyses demonstrated that the six-factor structure (i.e., the dimensional structure) of the MOGQ was satisfactory for the Turkish version. The scale was also reliable (i.e., internally consistent with a Cronbach’s alpha of 0.91 for coping/escape, 0.92 for recreation, 0.88 for fantasy, 0.91 for skill development, 0.87 for social, and 0.89 for competition) and showed adequate convergent and criterion-related validity, as indicated by statistically significant positive correlations with average time daily spent playing games during last year, IGDS9-SF, and EGMQ scores. These findings support the Turkish version of the MOGQ as a valid and reliable tool for determining the motives for online gaming among young adults.